Characteristics in bilayer organic light-emitting diodes with variation of the film thickness - Lee, KJ; Yu, JW; Kim, JK; Kim, YC; Park, JH; Park, OO (TAYLOR & FRANCIS LTD, 2004)
We fabricated bilayer polymer light-emitting diodes (PLED) with Poly(9,9'-dihexylyflourene-2,7-divinylene-m-phenylenevinylene-stat-p-phenylenevinylene) (PTHFMPPV) and poly(N-vinylcarbarzole) (PVK) as an emitting layer and a hole transport layer respectively. The thickness of each, layer was varied, white lite total thickness was controlled to be constant as 110nm. We observed electroluminescence, photoluminescence and current-voltage-luminescence characteristics of these bilayer devices and a single layer device with PDHFMPPV polymer as a light emitting layer for comparison. The quantum efficiencies of the bilayer devices were enhanced up to two about orders magnitude compared with the single-layer device.
Keywords: ENERGY-TRANSFER; ELECTROLUMINESCENCE; LUMINESCENCE; COPOLYMER; BLENDS